Teacher Education in Lifelong Learning Developing Professionalism as a Democratic Endeavour - Iredale, Alison (Springer International Publishing, 2018)
This book promotes the idea that professionalism among teachers should be marked by democratic relations, rather than by managerialism and performance management. It provides a thorough investigation of issues around the participation of trainee teachers in the Lifelong Learning Sector, by reflecting on their experiences and questioning how well initial teacher education prepares teachers as professional practitioners in the sector. The reflexive nature of the book promotes a deep discussion of the nature of professionalism, drawing upon the works of John Dewey, Michel Foucault and Pierre Bourdieu, and places initial teacher education in the Lifelong Learning Sector firmly within the policy and ideological context of regulation, audit and control. It also illuminates pertinent discussions around teacher agency through a consideration of confidence, excellence, and routinised practices. Finally, the book takes us 'through the looking glass' to reveal the tensions within the teacher education curriculum as it prepares trainee teachers for a ready-made world, whilst at the same time attempting to encourage principles of social justice, inclusive practice and education as a democratic endeavour. It will be compelling reading for students and researchers working in Education and Sociology, particularly those with an interest in lifelong learning and teacher training.